; Economic situation of Moldavians farm enterprises - Dragoés Cimpoješ; Eberhard Schulze (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2006)
2003 104 - . - - (, - ), , - . , 60. - " ", . / , , - , . , - - . . , / . - , 1 / - . . - . , . , - . - . , / - , . / . , - , . – – The given Discussion Paper represents the results of a questionnaire, conducted in 2003, on basic economic questions in 104 Moldavian farm enterprises. The received results continue the cycle of research activities concerning the privatization and restructuring of farm enterprises in different countries of Central and Eastern Europe, are written on a similar structure, allowing to carry out a comparative analysis between the countries of the region. To some extent, the given paper can be regarded as a continuation of the Discussion Paper 60. As the base for the analysis the standardized questionnaire has been put forward, developed by IAMO, being advanced and adapted by the authors to local conditions. Study of the activity of farm enterprises of different legal forms has shown that despite the fact that all corporate farms operate in market relations, only limited liability companies can be considered really market oriented. As a whole, corporate enterprises are very big, while peasant farms - very small and fragmented. Land market is in the stage of developing. Among the market mechanisms, short-term land lease is wide spread. Because of low demand, the average price of agricultural land is very low. Many works are carried out manually in the surveyed farms. Very high correlation dependence has been revealed between the legal form of enterprises and the amount of machinery. At the same time, the amount of machinery in no way influences the total number of workers. The state of technical park of the surveyed farms, for the expired period, has been significantly improved. Leasing and own means of farms are the main sources of procurement of new machinery. One of the most actual problems with which the agricultural producers face with - the market, namely the low prices and delayed payments for sold production. The basic channels of distribution of agricultural products are commercial enterprises and procuring organizations. Despite of the difficulties, the most part of the interviewed managers are satisfied with how their farms develop and look in the future with optimism.
urn:nbn:de:gbv:3:2-1715
Keywords: Q12; D2; O1; O4; P3; 330; Consolidation; land lease; production factors; buy-sell; work force; legal forms; Moldova; -; -